2015
DOI: 10.1007/s10508-014-0477-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Intoxication and Arousal on Approach/Avoidance Biases Toward Sexual Risk Stimuli in Heterosexual Men

Abstract: This study tested the effects of alcohol intoxication and physiological arousal on cognitive biases toward erotic stimuli and condoms. Ninety-seven heterosexual men were randomized to 1 of 6 independent conditions in a 2 (high arousal or control) × 3 (alcohol target BAC = 0.08), placebo, or juice control) design and then completed a variant of the Approach Avoidance Task (AAT). The AAT assessed reaction times toward approaching and avoiding erotic stimuli and condoms with a joystick. Consistent with hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
1
23
1
Order By: Relevance
“…This acute effect is consistent with the Alcohol Myopia Model (see Giancola et al, 2010), which posits that intoxication narrows attention to more salient, typically instigatory cues (e.g., sexual arousal, Simons et al, 2016), while impairing the ability to attend to less salient inhibitory cues (e.g., woman's reluctance). In natural drinking settings, pharmacological effects may be enhanced by alcohol expectancy effects (Abbey, 2011), i.e., the belief that alcohol enhances sex (George et al, 2000) and that drinking women are more interested in sex (George et al, 1995).…”
Section: Effects Of Alcohol On Sexual Assault Perpetrationsupporting
confidence: 78%
“…This acute effect is consistent with the Alcohol Myopia Model (see Giancola et al, 2010), which posits that intoxication narrows attention to more salient, typically instigatory cues (e.g., sexual arousal, Simons et al, 2016), while impairing the ability to attend to less salient inhibitory cues (e.g., woman's reluctance). In natural drinking settings, pharmacological effects may be enhanced by alcohol expectancy effects (Abbey, 2011), i.e., the belief that alcohol enhances sex (George et al, 2000) and that drinking women are more interested in sex (George et al, 1995).…”
Section: Effects Of Alcohol On Sexual Assault Perpetrationsupporting
confidence: 78%
“…The mechanisms by which alcohol alters sexual arousal are complex and dose-dependent (George and Stoner 2000;Prause et al 2011). The expectancy of alcohol drinking or actual alcohol drinking increased the time of viewing erotic pictures (George and Stoner 2000;Lang 1985) and approach toward erotic stimuli (Simons et al 2015), indicating an increase in sexually oriented behavior. Laboratory studies have shown that higher doses of alcohol suppress penile tumescence and vaginal blood volume and increase the latency to orgasm, thus decreasing objective indices of genital arousal and sexual performance (for review, see (George and Stoner 2000;Prause et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption has also been implicated in sexual disinhibition and sexual risk taking (George and Stoner 2000;Hesse and Tutenges 2008). Alcohol prolonged the viewing of erotic pictures (Lang 1985) and also produced an approach bias toward erotic stimuli compared with placebo (Simons et al 2015). However, unclear is whether alcohol actually enhances sexual arousal and desire or produces disinhibition (Prause et al 2011), and we are unaware of studies that evaluated whether alcohol acutely enhances subjective sexual arousal by sexual/erotic visual stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these effects were attenuated by working memory [64] and affective decision-making ability [65]. In addition, an experiment by Simons et al [66] showed that acute alcohol intoxication was associated with implicit approach biases toward sexual cues paired with a weaker approach toward condom stimuli. These studies did not focus on MSM but provide supportive evidence of the potential interactions among implicit cognition, executive function, and alcohol intoxication.…”
Section: General Conclusion: Part Imentioning
confidence: 99%